2017
DOI: 10.1007/s12035-016-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein alters differently gene expression of Sirts, PARPs and other stress response proteins: implications for neurodegenerative disorders

Abstract: Alpha-synuclein (ASN) is a presynaptic protein that can easily change its conformation under different types of stress. It’s assumed that ASN plays an important role in the pathogenesis of Parkinson’s and Alzheimer’s disease. However, the molecular mechanism of ASN toxicity has not been elucidated. This study focused on the role of extracellular ASN (eASN) in regulation of transcription of sirtuins (Sirts) and DNA-bound poly(ADP-ribose) polymerases (PARPs) - proteins crucial for cells’ survival/death. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 98 publications
2
38
0
1
Order By: Relevance
“…SIRT1 deacetylase activity mediates clearance of α-syn through light chain 3 (LC3) mediated autophagy to protect against PD pathology (Guo et al, 2016). Moreover, extracellular α-syn accumulation leads to mitochondrial dysfunction and a reduction of SIRT1 expression (Motyl et al, 2018). One the other hand, the upregulation, and activation of SIRT1 could activate peroxisome proliferator-activated receptor γ co-activator 1 (PGC-1α) to confer DA neuron protection against oxidative stress (Mäkelä et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 deacetylase activity mediates clearance of α-syn through light chain 3 (LC3) mediated autophagy to protect against PD pathology (Guo et al, 2016). Moreover, extracellular α-syn accumulation leads to mitochondrial dysfunction and a reduction of SIRT1 expression (Motyl et al, 2018). One the other hand, the upregulation, and activation of SIRT1 could activate peroxisome proliferator-activated receptor γ co-activator 1 (PGC-1α) to confer DA neuron protection against oxidative stress (Mäkelä et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that LAG3 proteolytic cleavage can be carried out by ADAM17 and ADAM10, two membrane metalloproteases, resulting in the generation of sLAG3 [74]. Interestingly, extracellular α-synuclein may downregulate the expression of ADAM10, whose role has been already established in Alzheimer's disease pathogenesis [75]. Thus, a low activity of ADAM17 and ADAM10 may represent the reason of decreased sLAG3 levels in the CSF of PD patients [40].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Instead of invoking the downregulation of pro-survival gene expression [62][63][64], we provide an alternative mechanistic explanation to how the transcriptional derepression of a pro-apoptotic gene can participate in the pathogenesis of neurodegenerative disorders. Instead of invoking the downregulation of pro-survival gene expression [62][63][64], we provide an alternative mechanistic explanation to how the transcriptional derepression of a pro-apoptotic gene can participate in the pathogenesis of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%